Implementation of Information Technology Balanced Scorecardin and Agriculture Organisation - Romansyah, Yusep; Mubarok, Husni; Yunanto, Rio (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
Sentra Pelayanan Agribisnis (SAPA) is an agricultural organization owned and operated by a farmer community in Sukabumi, West Java, Indonesia. SAPA adopts information technology (IT) to improve the effectivity of its internal communication. SAPA started IT adoption by a careful planning. The step includes organizing the map of IT strategy and formulating the key performance indicators. The purpose of this research is to arrange a strategy map of SAPA IT division, to formulate the key performance indicators using Balanced Scorecard approach, and to implement as a mobile web application. Results of this research include a strategy map of SAPA IT division, key performance indicators, and a prototype of mobile web application. It can be concluded that IT adoption supported by a strong leadership improves effectivity of the information flows within the researched agriculture organisation.